TWO CONCEPTS OF UNDERSTANDING THE ACTING SUBJECT: ARENDT AND WOJTYŁA. - MAZUR, PIOTR (Annals of Philosophy / Roczniki Filozoficzne, 2026)
The purpose of this article is to compare the conceptions of the subject of action and of human nature and condition as seen by Hannah Arendt and Karol Wojtyła. Wojtyła, in accordance with the Thomistic tradition, focuses on the person as the author of moral action ("act"), through which his nature (humanity) and unique mode of existence are manifested. Arendt, on the other hand, emphasises the importance of individual subjects through action demonstrating their presence in the public sphere. In opposition to the concept of nature, the German philosopher emphasises the importance of the condition as a human mode of existence subject to both permanent and changing external conditions. Although Arendt’s and Wojtyła’s concepts differ significantly, they share an interest in human action, and their visions of nature and condition complement each other.